DESIGN PROTOTYPE ONLINE SHOP DAGING AYAM SEGAR BERBASIS WEBSITE PADA UD. KAZAIN BROILER DI KOTA SERANG - Purnama, Eris Dwi; Permana, Basuki Rakhim Setya (Jurnal Ilmiah Sistem Informasi, 2023)
Kazain Broiler is a Fresh Cut Chicken Supplier offering chicken pieces at affordable and cheap prices. This chicken shop, which is located in Serang City, has a complete list and list of chicken pieces. The development of digitalization is increasingly rapid and fulfills all aspects of human life throughout the world. Not only that, updates on the development of information technology are increasingly providing easy services to every user. Online shop or online business today is not something foreign to the court community in any corner of the world, especially the Indonesian people, whether they use the internet in their daily life or not. Computers are very popularly used as a tool for various activities, for example in business administration activities for trading businesses. UD. Kazain Broiler is the best poultry supplier in Serang City which offers high quality chicken meat at affordable prices. By having various types of fresh chicken that will keep the food healthy, nutritious and delicious. The quality chicken offered by UD.Kazain Broiler goes through various processes to make it hygienic and healthy for consumers. UD. Kazain Broiler is the best poultry supplier in Serang City which offers high quality chicken meat at affordable prices. By having various types of fresh chicken that will keep the food healthy, nutritious and delicious. The quality chicken offered by UD.Kazain Broiler goes through various processes to make it hygienic and healthy for consumers. Not only that, UD. Kazain Broiler also sells and supplies chicken meat to various food industries and big events such as celebrations, weddings, celebrations, and big day events. UD.Kazain Broiler in carrying out its main sales currently still uses conventional techniques, it still requires stationery, paper and calculators to manage buying and selling data. The owner wants every sale proceeds to have a recapitulation system and relevant financial reports. Since the implementation of the first PSBB and PPKM on April 28, 2020, the relatively quiet market conditions have caused stockpiles of chicken meat to accumulate and not be distributed. As a result, consumers cannot buy the desired meat if the stall selling the desired meat partners runs out and has to seek or wait for information from other partners. For this reason, an integrated information system is needed because it is considered to save more time and costs. So that consumers don't have to go around looking for meat stocks that are still there that consumers need. Based on the results of observations and interviews that have been carried out at UD. Kazain Broiler in Serang City, the researchers feel the need to build a system as well as a tool that is integrated with the inventory information system so that each partner can exchange information and overcome the problems above. In this design, the website prototype was chosen because it has easy access for anyone to do without the need to download it first